The Economic Impact of Murabahah Financing On PT. PNM Mekar Syariah In Increasing The Welfare Of Pre-Prospered Women - Saputri, Deni; Miswardi; Nasfi, Nasfi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2021)
The main problem that the authors study in this study is how the economic impact of murabahah financing on PT. The general objective to be achieved in this research is to find out how the economic impact of murabahah financing on PT. This research is a qualitative field research. This research is descriptive and emphasizes the analysis side. Process and meaning are highlighted in qualitative research on the theoretical basis that is used as a guide to focus on research in accordance with the facts on the ground. The data collection method in this study is by observation and interviews. The results of the study found that in general present PT. PNM Mekar Syariah in Banuhampu District and unsecured murabahah financing distributed by PT. PNM Mekar Syariah has a positive but not significant impact on improving the welfare of underprivileged women in Banuhampu sub-district from an economic perspective.